A perícope da restauração de Pedro em Jo 21,15-19 no contexto do Evangelho segundo João. - Guerra, Linaldo de Souza (2019)
With this work, we study the pericope of John 21,15-19, in order to understand the meaning of the restoration of Peter, in the dialogue between Jesus and Peter. Therefore, this work was divided into three chapters. The first chapter intend to present introductory questions of the Gospel according to John, such as authorship, date, recipients, literary style, vocabulary etc. The second chapter deals, firstly, with the themes present in the narratives of Jn 21 and, secondly, with a widely disputed question, namely, the integration of this chapter (21) into the corpus of this Gospel. The third chapter, in turn, deals with the analysis of the pericope in question (Jn 21, 15-19), which was done considering its literary, vocabulary and theological aspects. At this stage, we sought to know the theological intentions in the service of which the evangelist employed some literary artifices, especially what concerns the structuring of the dialogue between Jesus and Peter in three sections, each containing a question (from Jesus to Peter) repeated three times, a response (from Peter to Jesus) repeated three times a mandate (from Jesus to Peter); repeated three times. For the accomplishment of the present research, bibliographical research and analysis of biblical texts was used. The meaning of Peter's restoration in the pericope of Jo 21,15-19 is discussed in the present work.